2018
DOI: 10.1002/clc.23107
|View full text |Cite
|
Sign up to set email alerts
|

Where we live: The impact of neighborhoods and community factors on cardiovascular health in the United States

Abstract: While the prevalence of cardiovascular risk factors has decreased in the United States in recent years, cardiovascular disparities by sex and race persist. Among the factors contributing to these disparities is the physical environment in which individuals live. Neighborhood characteristics, ranging from air pollution exposure to residential segregation, have been found to be related to cardiovascular health (CVH) and stroke risk. Through the use of cross‐sectional, longitudinal, and analytic regression modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 18 publications
(34 reference statements)
0
34
1
Order By: Relevance
“…Additionally, results from a study of 15 American states showed that an increase in cardiovascular and respiratory illness was linked to tree loss [25]. Xiao et al found that participants were more likely to have ideal cardiovascular health (CVH) rather than poor CVH in neighbourhoods that offered physical activity resources (19%), or a walking/physical activity environment (20%) [26]. The relationship between urban green space and cardiovascular health has been revealed by a number of studies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, results from a study of 15 American states showed that an increase in cardiovascular and respiratory illness was linked to tree loss [25]. Xiao et al found that participants were more likely to have ideal cardiovascular health (CVH) rather than poor CVH in neighbourhoods that offered physical activity resources (19%), or a walking/physical activity environment (20%) [26]. The relationship between urban green space and cardiovascular health has been revealed by a number of studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to poor access to healthy foods and exercise, individuals living in poverty are exposed to disproportionate environmental toxicities. Multiple studies connect the stress of living in low-income, under-resourced neighborhoods to chronic diseases (10,11). Elevated exposure to stressors begins in childhood, and ACEs are more common in low-income neighborhoods (12).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of environment, as the most important spatial carrier of exercise in the urban space [ 8 ], and having other advantages such as improving air quality, enhancing the social communication, and reducing pressure [ 9 ], green spaces have been widely found to be associated with cardiovascular health [ 10 , 11 , 12 , 13 , 14 , 15 ]. According to the U.S. National Environmental Protection Agency, green space is defined as land that is partly or completely covered with grass, trees, shrubs or other vegetation, including parks, squares, playgrounds, residential yards, schoolyards, public seating areas.…”
Section: Introductionmentioning
confidence: 99%
“…There are a growing number of studies focusing on the impacts of green space on cardiovascular health [ 10 , 11 , 12 , 13 , 14 , 15 ]. The involving green space factors include the scale, layout, physical activity resources, and the use [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation